Book review: Steve Keen, Debunking economics - Darío Ibarra ZAVALA (Annals of Spiru Haret University Economic Series, 2014)
The world has reduced its economic growth rates since several decades ago. Besides, there have been periods of economic “moderation” and economic crisis. Prior to the crisis of 2008, the world seemed to be running properly, but suddenly things changed and mainstream economists were not able to explain the account of this crisis. .....